EFEKTIVITAS KOMUNIKASI INTERPERSONAL DOSEN DAN MAHASISWA DALAM PROSES BIMBINGAN SKRIPSI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM FAKULTAS TARBIYAH DAN KEGURUAN, UIN AR-RANIRY - desi isra muliana; hamdani m.syam (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAK Penelitian ini berjudul “Efektivitas Komunikasi Interpersonal Dosen Dan Mahasiswa Dalam Proses Bimbingan Skripsi Pada Mahasiswa Program Studi Pendidikan Agama Islam Fakultas Tarbiyah Dan Keguruan, UinAr-Raniry”. Penelitian ini bertujuan untuk mengetahui efektivitas komunikasi interpersonal antara dosen dan mahasiswa Prodi Pendidikan Agama Islam Universitas UIN Ar-Raniry dalam proses bimbingan skripsi. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Subjek penelitian ini ialah tujuh dosen dan tujuh mahasiswa Prodi Pendidikan Agama Islam Universitas UIN Ar-Raniry yang dipilih dengan teknik purposive sampling. Teknik pengumpulan data dilakukan dengan wawancara dan dokumentasi. Penelitian ini menggunakan teori Fundamental Interpersonal Relations Orientations (FIRO).Hasil penelitian dapat diketahui bahwa komunikasi interpersonal antara dosen dan mahasiswa Prodi Pendidikan Agama Islam dalam proses bimbingan skripsi belum berjalan secara efektif ditinjau dari indikator kesetaraan, empati, dukungan, rasa positif, dan hanya indikator keterbukaan yang terlihat efektif. Hal ini disebabkan oleh factor seperti kurangnya kedisiplinan mahasiswa dalam menjaga waktu bimbingan yang telah ditetapkan dosen dan susahnya mahasiswa menjumpai dosen pembimbing dikarenakan dosen bersangkutan memiliki jadwal mengajar serta aktivitas lainnya. Faktor lain yang menghambat penyelesaian skripsi mahasiswa Prodi Pendidikan Agama IslamUniversitas UIN Ar-Raniry ialah sulitnya mahasiswa dalam menentukan masalah dari judul yang ingin diangkat, mengkonsep isi skripsi, mengoreksi teknik penulisan, menentukan metode penelitian yang digunakan, serta kurangnya motivasi dan minat mahasiswa untuk mengerjakan skripsinya dan mencari referensi, sehingga berdampak terhadap waktu penyelesaian skripsi dan kualitas skripsinya. The Effectivity of Interpersonal Communication between Lecturers and Students during Undergraduate Thesis Counselling at The Department of Islamic Religious Education of The Faculty of Tarbiyah and Teachers’ Training, Islamic State University of Ar-Raniry”ABSTRACT The title of this research is “The Effectivity of Interpersonal Communication between Lecturers and Students during Undergraduate Thesis Counselling at The Department of Islamic Religious Education of The Faculty of Tarbiyah and Teachers’ Training, Islamic State University of Ar-Raniry”. The aim of this research is to evaluate the interpersonal communication between lecturers and students at the Department of Islamic Religious Education of Islamic State University of Ar-Raniry during undergraduate thesis counselling. This research is descriptive in nature and employs qualitative approach. The subjects of this research are seven lecturers and seven students of the Department of Islamic Religious Education of Islamic State University of Ar-Raniry, selected by purposive sampling. The data collecting techniques were carried out through interview and documentation. The main theory of this research is Fundamental Interpersonal Relations Orientations (FIRO). From the result, it can be observed that interpersonal communication between the lecturers and the students of the Department of Islamic Religious Education has not been effective according to indicators of equality, empathy, supportiveness and positiveness, while it only has been effective according to the indicator of openess. This was generated by factors such as the lack of student’s discipline in keeping the counselling time which has been priorly decided and the difficulties for the students to meet the lecturers because of the lecturers have teaching schedule or other activities. Another obstructive factor of the student’s undergraduate thesis accomplishment in the Department of Islamic Religious Education of Islamic State University of Ar-Raniry is the difficulties for the students to decide the problem of the thesis title, to conceptualize the thesis content, to correct the writing technique, to choose the research methodology, to be motivated and passionate to accomplishe the thesis and to look for the references, thus impacted the accomplishment duration and quality of their undergraduate thesis. Keywords: Effectivity, Interpersonal Communication, Lecturer and Student, Undergraduate Thesis